2022
DOI: 10.3390/diagnostics12010214
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Translocation and Perinatal Asphyxia/Hypoxia: A Systematic Review

Abstract: The microbiome is vital for the proper function of the gastrointestinal tract (GIT) and the maintenance of overall wellbeing. Gut ischemia may lead to disruption of the intestinal mucosal barrier, resulting in bacterial translocation. In this systematic review, according to PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines, we constructed a search query using the PICOT (Patient, Intervention, Comparison, Outcome, Time) framework. Eligible studies reported in PubMed, up to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For example, intestinal damage resulting from low level ischemia or inflammation may share common pathways with placental insufficiency. 38 Increased microbial translocation has also been associated with reduced progesterone levels among pregnant PWLHIV, 39 which has been associated with preterm birth and may be associated with stillbirth. 40 Additional studies are needed to confirm our findings and to elucidate the potential mechanisms linking these maternal EED biomarkers to the risk of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intestinal damage resulting from low level ischemia or inflammation may share common pathways with placental insufficiency. 38 Increased microbial translocation has also been associated with reduced progesterone levels among pregnant PWLHIV, 39 which has been associated with preterm birth and may be associated with stillbirth. 40 Additional studies are needed to confirm our findings and to elucidate the potential mechanisms linking these maternal EED biomarkers to the risk of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Matara and co-workers, in a recent systematic review [ 31 ], suggested that the GI tract is a target organ, with high sensitivity to ischemia–hypoxia, and even short periods of ischemia may cause significant local tissue damage. Fetal hypoxia and perinatal asphyxia reduce bowel motility, especially in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between microbiome and host is dynamic and many factors (such as genetic background, maternal diet prior to and during pregnancy, maternal microbiome, mode of delivery, gestational age, perinatal stress, infections during pregnancy and during the perinatal or neonatal period, feed type of neonates and especially of preterm infants, and other environmental factors such as temperature, humidity, pH, and oxygen levels in the tissues type) modulate the infants’ microbiome constitution and its dynamic relationship with the host, which can be transformed from ‘synbiotic’ to ‘dysbiotic’ and life-threatening [ 95 , 96 ].…”
Section: Development Of the Gut Microbiomementioning
confidence: 99%